2009
DOI: 10.1055/s-2008-1039198
|View full text |Cite
|
Sign up to set email alerts
|

Dribbling Diversion in Y‐V Glanuloplasty Modified Mathieu Repair

Abstract: An indwelling transurethral catheter obviates urinary retention and avoids distressing postoperative micturation. It minimises the chance of urethrocutaneous fistula and meatal stenosis in Y-V glanuloplasty modified Mathieu repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Nevertheless, some argue the need for a urethral catheter or stent, as non-catheter repair has higher complication rates. Others have found that the urethral catheter does have the advantage of preventing urinary retention and early urethrocutaneous fistula after the repair [10,11,12]. Thus, the decision depends on the individual surgeon's preference and there has been little scientific evidence behind the choice.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some argue the need for a urethral catheter or stent, as non-catheter repair has higher complication rates. Others have found that the urethral catheter does have the advantage of preventing urinary retention and early urethrocutaneous fistula after the repair [10,11,12]. Thus, the decision depends on the individual surgeon's preference and there has been little scientific evidence behind the choice.…”
Section: Introductionmentioning
confidence: 99%
“…Rich et al demonstrated that long-term results with overnight stenting for patients with distal and mid-penile hypospadias were similar to reported data [19]. In animal studies [16][17][18][19][20][21], it has been shown that in Snodgrass repair tissue healing starts by re-epithelialization of the incised plate. For partial reepithelialization five days and for complete epithelialization and normal urothelium two weeks are required [16].…”
Section: Discussionmentioning
confidence: 65%
“…There was no stenosis of the urethral meatus in either group of patients. Fathi and Pintér [14] evaluated the impact of an indwelling transurethral catheter on surgical outcome and postoperative micturation with Y-V glanuloplasty modified Mathieu repair for primary hypospadias. They reported that a transurethral catheter avoids distressing postoperative micturation and minimizes the chance of urethrocutaneous fistula and meatal stenosis.…”
Section: Discussionmentioning
confidence: 99%